Predictors Associated with Forgotten Knee in Patients with Total Knee Arthroplasty Based on Multivariable Linear Regression - Peifang Li; Jingying Xie; Ning Ning; Jiali Chen (Orthopaedic Surgery, 2024)
Objective Existing studies have conflicting results about the predictors of forgotten joints in patients with total knee arthroplasty (TKA), and the relationship between psychosocial factors and forgotten knees is unknown. The purpose of this study was to confirm predictors for the forgotten joint in TKA patients. Methods This was an observational, prospective longitudinal study. A total of 205 patients who underwent TKA and a 6‐month follow‐up were included between August 2020 and September 2021. Demographic characteristics, clinical characteristics, and psychosocial variables were collected before TKA surgery (T0). The forgotten joint score (FJS) was taken before TKA surgery (T0) and at 1 month (T1), 3 months (T3), and 6 months (T6) after TKA surgery. The psychosocial variables were also completed at T6. Bivariate and multivariable linear regressions (LR) were performed to screen the predictors associated with FJS (T6). Results Patients who underwent TKA in our study had a mean FJS of 20.3 ± 12.2 before surgery, 15.9 ± 10.3 at 1 month, 28.7 ± 12.6 at 3 months, and 40.3 ± 12.5 at 6 months. The predictors were sex, combined musculoskeletal disorders (MSD), operation time, FJS (T3), range of motion (ROM) (T6), pain score (T6), Groningen orthopaedic social support scale (GO‐SSS) score (T6), and the generalized anxiety disorder scale (GAD) score (T6). The data satisfied the assumptions of multivariable linear regressions. The multiple R2of LR was 0.71, and the adjusted R2 was 0.70. The F‐statistic of the LR model was 59.5 (p < 0.000). Conclusion Our study revealed the level of forgotten knee decreased slightly from preoperation to 1 month postoperatively and then increased from 1 month postoperatively to 6 months postoperatively in TKA patients. The main predictors associated with the FJS at 6 months after surgery were sex, combined MSD, operation time, FJS (T3), ROM (T6), pain score (T6), GO‐SSS score (T6), and anxiety (T6).